PHRASE THEORY: PHRASE TYPES AND SUBTYPES: COORDINATE, SUBORDINATE AND PREDICATIVE PHRASES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the relationship between sentence typology, clause types, and clause structure within the framework of Cognitive Grammar (CG). It highlights how Cognitive Grammar, developed by Ronald Langacker, challenges traditional syntactic theories by emphasizing the role of human cognition in language. The article defines and discusses the three primary clause types—declarative, interrogative, and imperative—showing how they align with different communicative intentions and cognitive processes. I